Performance measurement and management control behavioral implications and human actions - Davila, Antonio; Epstein, Marc J.; Manzoni, J. F. (Emerald, 2014)
This new volume contains selected papers that were presented at the 2013 conference on performance measurement and management control focusing on behavioral implications and human actions associated with the use of performance measurement and management control systems.
Includes index.
Keywords: Accounting -- Congresses.; Performance -- Research -- Congresses.; Managerial accounting -- Congresses.; elektronické knihy; electronic books